2018
DOI: 10.14744/eej.2018.09609
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the decision-making of direct pulp capping procedures amongst Turkish dental practitioners

Abstract: To examine the factors affecting the decision-making of direct pulp capping procedures amongst Turkish dental practitioners. Methods: A total of 378 Turkish dentists participated in the survey. The questionnaire comprised three sections. The first part comprised questions regarding demographic features. The second part comprised; questions on how treatment plans change according to factors such as pulp perforation position, number, size, how it occurred, and patient age. The third part composed of questions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 35 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…Therefore, in the literature, the success of DPC has been discussed with great controversy. Moreover, the risk perception for the success of DPC of each dentist isn't similar that leads to different treatment approaches 6 . It is also observed that in clinical circumstances where chances of success of DPC anticipated by the clinician are low, they opt for more invasive surgical approaches, including pulpotomy or RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the literature, the success of DPC has been discussed with great controversy. Moreover, the risk perception for the success of DPC of each dentist isn't similar that leads to different treatment approaches 6 . It is also observed that in clinical circumstances where chances of success of DPC anticipated by the clinician are low, they opt for more invasive surgical approaches, including pulpotomy or RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in accordance with other researches. (6,24) It suggested that irrespective of inflammatory response of the pulp CH was the most selected material for direct capping of pulp. Most likely the reason behind this could be, the training of the participants during their clinical education, ability of CH to form reparative dentine and cost effectiveness and continuation of learnt techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, each dentist has different treatment approaches for the success of DPC. (6,7) The choice of dental material predicts the prognosis of vital pulp therapy. Several materials are available for pulp capping procedure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations